The somatechnics of enfreakment: literary articulations of the body - Pettersson, Lin Elinor (My University, 2015)
Lately, the Victorian freak show has attracted scholarly and literary attention alike. New critical approaches to the freak show set the European exhibition of human corporeal deviance apart from the American side show as popularized by P. T. Barnum. Topics ranging from, the social context of freakery (Tromp et al. 2008) and the cultural history of enfreakment (Kérchy, Zittlau et al. 2012), to the significance of disability in Victorian literature (Craton 2009) and the spectacle of deformity (Durbach 2009) have been addressed by scholars who are concerned with the ethics of embodied difference. In the twenty-first century, the Victorian world of spectacle has emerged as a separate ramification within neo-Victorian literature—this densely visual narrative mode sets up an apt socio-historical frame to delve into the social construction of embodied subjectivities. The present paper explores neo-Victorian enfreakment through the lens of somatechnics reading “[e]mbodiment as the incarnation or materialisation of historically and culturally specific discourses and practises” (Sullivan and Murray, 3). My principal aim is to examine the epistemological speculation of (un)intelligible corporeality by analysing the intersection of gender and ideology on the body. By delving into neo-Victorian reinventions of the divergent body, I seek to address the formation and representation of the complexities of the embodied self. With this objective in mind, I will analyse how the neo-Victorian mode interlocks the Victorian freak-show discourse with the reader perspective to bring subjective responses to corporeality, humanity and normativity to the forefront, and in doing so, turns an exploitative space as the freak show into a site of self-reliance, self-expression and even fulfilment.
Keywords: Literatura inglesa - S. XIX - Historia y crítica; Cuerpo humano en la literatura; Malformaciones congénitas en la literatura; Somatechnics; Freak; Neo-Victorianism; Body; Literature; Embodiment